A method for increasing the supersolvus critical strain for recrystallization in single-crystal superalloys - Lin, Sicong (2023)
Recrystallization, possibly triggered during heat treatments by plastic strains of only 1–2%, is highly deleterious to Ni-based single-crystal superalloys. Herein, we successfully recover plastic deformation and enhance the supersolvus critical strain for recrystallization by ramping the annealing temperature slowly from 1100 °C to γ′-solvus point. This preempts recrystallization during the subsequent supersolvus solutionizing treatment. The proposed method is validated in single-crystals compressed to 5.9% plastic strain at room temperature. After supersolvus solutionizing, an almost dislocation-free single-crystal with uniformly distributed γ′-precipitates is obtained. The proposed method offers a practical means to bring down the overall expenses of single-crystal turbine blades.